2017
DOI: 10.1158/2326-6066.cir-16-0221
|View full text |Cite
|
Sign up to set email alerts
|

Converting Lymphoma Cells into Potent Antigen-Presenting Cells for Interferon-Induced Tumor Regression

Abstract: Anti-hCD20 is a therapeutic monoclonal antibody (mAb) that is clinically used to treat B-cell lymphoma. Some lymphomas are resistant to anti-hCD20; others relapse after treatment with anti-hCD20. Using a syngeneic immunocompetent mouse model, we observed that targeting lymphoma with interferon-α (IFNα) abolished resistance of B-cell lymphoma to anti-CD20 while limiting interferon (IFN)-associated systemic toxicity in the host. Control of tumors by a fusion of anti-CD20 and IFNα (anti-CD20-IFNα) depended on exi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Systemic delivery of type I IFNs is usually used clinically, but high-dose need to be administrated to achieve high-serum concentration for effective therapeutic effect accompanied with dose-limiting toxicities. Arming tumor-targeting antibodies with cytokines has been shown to be a potent strategy for the local delivery of immunomodulatory molecules 19 22 . However, it is difficult to identify tumor-specific molecules for therapeutic targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic delivery of type I IFNs is usually used clinically, but high-dose need to be administrated to achieve high-serum concentration for effective therapeutic effect accompanied with dose-limiting toxicities. Arming tumor-targeting antibodies with cytokines has been shown to be a potent strategy for the local delivery of immunomodulatory molecules 19 22 . However, it is difficult to identify tumor-specific molecules for therapeutic targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrotic tissue and normal thyroid tissue were consistent with echogenic structures within or around the lesions. Densely and uniformly proliferated lymphoma cells in the lesion were possibly related with an enhanced posterior echo [40]. HT is considered as a risk factor for thyroid lymphoma development.…”
Section: Discussionmentioning
confidence: 90%
“…However, the function of IFNAR on host immune cells was not addressed. Using a syngeneic immunocompetent mouse model, Liao et al observed that targeting lymphoma with IFNα abolished resistance of B-cell lymphoma to anti-CD20 Ab while also limiting interferon (IFN)-associated systemic toxicity in the host (Liao et al 2017 ). Anti-CD20–IFNα fusion protein-mediated tumor control is dependent on existing tumor-infiltrating CD8+ T cells.…”
Section: Antibody Armed With Cytokines To Further Promote Adaptive Anmentioning
confidence: 99%
“…But the mechanism is unclear. In another combination therapy, PD-L1 blockade could enhance the antitumor efficacy of anti-CD20–IFNα and reduce relapse rates for advanced large tumors that are resistant to either anti-CD20 Ab or the anti-CD20–IFNα fusion protein (Liao et al 2017 ). IFN can increase PD-L1 expression on tumor cells and antigen presentation, each of which represents distinct mechanism of tumor control.…”
Section: Antibodies Targeting To Immune Inhibitory Receptors and Combmentioning
confidence: 99%